High volume online post-dilution hemodiafiltration: how relevant is it in chronic kidney disease? - Castro,Manuel Carlos Martins (2022)
ABSTRACT Online hemodiafiltration is potentially a superior mode of dialysis compared to conventional hemodialysis. However, prospective randomized controlled trials have failed to demonstrate such superiority. Post-hoc analyses of these trials have indicated that high volume post-dilution hemodiafiltration is associated with lower death rates than conventional dialysis. This study discusses whether the lower death rates ascribed to high volume hemodiafiltration are linked to convection volume or the time on dialysis needed to achieve high convection volumes.